Bulgaria : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report ;, 2021)
The economy contracted sharply amid two waves of COVID-19 infections, with the government providing sizable policy support. The outlook is very uncertain and the main challenge facing policymakers is to keep adjusting to changing circumstances. Over the medium term, structural reforms are needed that support inclusive income convergence toward advanced EU partners against demographic headwinds.